Acute hyperglycemia prevents dexmedetomidine-induced preconditioning against renal ischemia-reperfusion injury - Wang,Huaxin (2014)
PURPOSE: To investigate the effects of acute hyperglycemia on dexmedetomidine-induced preconditioning against renal ischemia-reperfusion injury. METHODS: Sprague-Dawley rats were randomly arranged to the normoglycemic (NG) or hyperglycemic group (HG), with each group further divided into sham (no I/R injury), I/R (ischemia-reperfusion) and dex (given by dexmedetomidine) groups. Acute hyperglycemia was induced by intraperitoneal injection (i.p.) of 25% glucose (3 g/kg) 45 min before ischemia. Dexmedetomidine (50 μg/kg, i.p.) was administrated 30 min before induction of ischemia. Renal function, histology, apoptosis, expression of Bax, Bcl-2 and phosphorylated AKT (p-AKT) were detected. RESULTS: I/R insult significantly increased the serum levels of blood urea nitrogen and creatinine, apoptotic tubular epithelial cells, expression of Bax and p-AKT, but decreased Bcl-2 expression. All these changes were further enhanced by hyperglycemia (p<0.05). In hyperglycemic condition, there was no statistically difference between the I/R group and Dex group in all the aforementioned detection indexes (p>0.05). CONCLUSION: Acute hyperglycemia attenuates dexmedetomidine-induced preconditioning against renal ischemia-reperfusion injury in non-diabetic rats.